Encoding and decoding of emotional speech : a cross-cultural and multimodal study between Chinese and Japanese / Aijun Li. - Li, Aijun (Heidelberg : Springer, 2015., 2017)
1 online resource (xxiii, 229 pages) : illustrations (some color).